DETRITAL ZIRCON AGES AND SOURCES OF MATERIAL FOR THE LOWER CAMBRIAN DEPOSITS OF THE MEL'GIN TROUGH OF THE BUREYA CONTINENTAL MASSIF - R. O. Ovchinnikov; A. A. Sorokin (Геодинамика и тектонофизика)
Bureya continental massif is one of the largest continental massifs in the eastern part of the Central Asian orogenic belt (CAOB) (Fig. 1), and knowledge of its geological structure is of fundamental importance in understanding the history of its formation.